Impediments of Students' English Language Speaking Skill in Two Selected Preparatory Schools in Wolaita Zone - Arega, Endale Endrias (European Scientific Journal, ESJ, 2017)
This study was intended to investigate impediments of students' English Language speaking with particular reference to Wolaita Sodo and Areka Preparatory Schools. The study also examines causes that account for these impediments. The subjects of the study were grade 11 students of the aforementioned schools. The samples of the study were 620 students out of 2,388 students in both preparatory schools; again 14 students and 8 English Language teachers were selected for the interview. The sample students were selected using simple random sampling technique. The data gathering instruments used were questionnaire, interview and classroom observation. To achieve the objectives, descriptive method of research design is used. To analyze the obtained data, both qualitative and quantitative methods of data analysis were used. The findings show that: lack of confidence from the student side, excessive use of mother tongue, preference of grammar and vocabulary than speaking, poor speaking background, shortage of vocabulary, teachers' emphasis on grammar and vocabulary, teacher centered way of teaching, large class size, lack of access to teaching aids, shortage of text books and references. Each of these factors was also caused by different problems such as: Classmates’ laughing when one makes a mistake while speaking; focusing on teaching grammar than speaking; focusing of exam questions mainly on grammar and vocabulary than speaking, nature of the English Text Book and teachers' experience of traditional teaching. Finally, the recommendations were forwarded based on the findings.